Sensitive Skin in the Indian Population: An Epidemiological Approach - Brenaut, Emilie; Misery, Laurent; Taieb, Charles (Frontiers in Medicine, 2019)
Sensitive skin is a very frequent condition, the prevalence of this syndrome has been studied in different countries in Europe, in United States and in Japan. The aim of the study was to evaluate the epidemiology of sensitive skin in the Indian population, like this has never been studied in this country. A representative nationwide sample of the Indian population aged 15 and over was selected. Individuals were selected as per the quota method (based on sex, age, householder profession, rural/urban location and region). In total, 27.9% of men and 36.7% of women declared having “sensitive” or “very sensitive” skin. The difference between the 2 sexes was very significant. Of these, 5.1% of men and 7.2% of women reported having “very sensitive” skin. The subjects complaining about “sensitive” or “very sensitive” skin were 2 to 4 times more likely to declare suffering from atopic dermatitis, acne, psoriasis, or vitiligo. They were 2 to 3 times more reactive to climatic factors, environmental factors, cosmetics and food intake. In conclusion, although less frequently reported than in other countries, sensitive skin is a frequent condition in India, affecting about one third of the population.